KECEMASAN IBU HAMIL TRIMESTER III MENGHADAPI PERSALINAN DAN PRAKTEK MENYUSUI DI ERA PANDEMI COVID -19 - Nur Hidayah; Tria Puspita Sari; Wiwik Puspita Dewi (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
The Anxiety of Third Trimester Pregnant Women Facing Childbirth and Breastfeeding Practices in the Era of the Covid-19 PandemicBackground: based on data from the Ministry of Health (Kemkes), there were 2,179 pregnant women who died. From this data, almost 18% of deaths are due to Covid-19. Anxiety in pregnant women can arise, especially in the third trimester of pregnancy until delivery. Based on data from the Indonesian Obstetrics and Gynecology Association (POGI) from January to April 2021, 536 pregnant women were exposed to COVID-19. A total of 16 people could not be saved. Pregnant women have a higher risk of exposure to COVID-19 than ordinary people. Objectives: :  This study aims to describe the anxiety of third trimester pregnant women facing childbirth and breastfeeding practices in the era of the covid-19 pandemic. Methods: The research design used was observational with a descriptive design. The number of samples is 13 third trimester pregnant women, and are willing to be respondents. Sampling technique with purposive sampling. Analysis and interpretation of data according to the calculation of the variable. Results: 84% of respondents did not feel anxious, 8% of respondents experienced mild anxiety, and 8% of respondents experienced severe anxiety when dealing with childbirth and breastfeeding practices in the era of the covid-19 pandemic. Conclusion: there are still pregnant women in the third trimester who experience mild and severe anxiety in dealing with childbirth and breastfeeding practices in the era of the covid -19 pandemic.